"คนดี สำคัญกว่าทุกสิ่ง": ญาติธรรมกับการสร้างการยอมรับพุทธทาสภิกขุในสังคมไทย พ.ศ. 2475 -2529 - ทิวาพร อภัยพัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
Thai society in the 1930s is considered a period of transition. Especially in terms of politics, bureaucrats such as members of the People s party came to play important roles in administrating and executing development policies in the modernizing Thai society. During that time, a young monk known as ‘Buddhadasa Bhikkhu’ announced his intentions to spread Buddhist knowledge in a new way, which he had discovered through studying the Buddha’s teaching on his own. Buddhadasa’s writings were widely accepted by Thai civil servants and intellectuals in the 1930s. This was because of a revival of enthusiasm in learning Thai Buddhism in Thai society during that period. Some Thai intellectuals came to be interested in studying Buddhism through logic and reason. They then proclaimed themselves as Buddhadasa’s followers. This thesis investigates the role of followers who supported Buddhadasa Bhikkhu and contributed to his success in spreading Buddhism. Buddhadasa’s followers come from all walks of life and from a great variety of political standings. A unique characteristic of Buddhadasa’s followers is that they consist of intellectuals with different political ideas and yet they are able to relate to one another though faith in the same monk without difficulty. Buddhadasa’s way of maintaining good relationship among his followers was to connect them through their interest in learning Buddhism rather than their political leaning. One of his personal journals is titled "Good people are the most important". This clearly shows Buddhadasa’s attitude in connecting with people. He did not evaluate or judge people from their political ideas. He believed that religious teachings make people into good people. Hence, anyone who studies Buddhism could be a follower of Buddhadasa Bhikkhu.